Comparative transcriptome analyses define genes and gene modules differing between two Populus genotypes with contrasting stem growth rates - Xiao Han; Yi An; Yangyan Zhou; Chao Liu; Weilun Yin; Xinli Xia (Biotechnology for Biofuels, 2020)
Abstract Background Wood provides an important biomass resource for biofuel production around the world. The radial growth of tree stems is central to biomass production for forestry and biofuels, but it is challenging to dissect genetically because it is a complex trait influenced by many genes. In this study, we adopted methods of physiology, transcriptomics and genetics to investigate the regulatory mechanisms of tree radial growth and wood development. Results Physiological comparison showed that two Populus genotypes presented different rates of radial growth of stems and accumulation of woody biomass. A comparative transcriptional network approach was used to define and characterize functional differences between two Populus genotypes. Analyses of transcript profiles from wood-forming tissue of the two genotypes showed that 1542, 2295 and 2110 genes were differentially expressed in the pre-growth, fast-growth and post-growth stages, respectively. The co-expression analyses identified modules of co-expressed genes that displayed distinct expression profiles. Modules were further characterized by correlating transcript levels with genotypes and physiological traits. The results showed enrichment of genes that participated in cell cycle and division, whose expression change was consistent with the variation of radial growth rates. Genes related to secondary vascular development were up-regulated in the faster-growing genotype in the pre-growth stage. We characterized a BEL1-like (BELL) transcription factor, PeuBELL15, which was up-regulated in the faster-growing genotype. Analyses of transgenic Populus overexpressing as well as CRISPR/Cas9-induced mutants for BELL15 showed that PeuBELL15 improved accumulation of glucan and lignin, and it promoted secondary vascular growth by regulating the expression of genes relevant for cellulose synthases and lignin biosynthesis. Conclusions This study illustrated that active division and expansion of vascular cambium cells and secondary cell wall deposition of xylem cells contribute to stem radial increment and biomass accumulation, and it identified relevant genes for these complex growth traits, including a BELL transcription factor gene PeuBELL15. This provides genetic resources for improving and breeding elite genotypes with fast growth and high wood biomass.